Miniimplantes como anclaje en ortodoncia (2006)
ABSTRACT: Control of anchorage is one of the most important factors for success during orthodontic treatment. Different mechanisms have been used in order to obtain this goal. They range from tooth structures to intraoral and extraoral oppliances. None of these methods provide optimum anchorage. In an attempt to overcome such limitations and obtain absolute anchorage, implants have been used. Among the different types of implants we find the osseointegrated implants, onplants, titanium mini plates and mini screws. Mini implants have been in use for the last two decades, during this period their use has notoriously increased due to their multiple advantages, such as, reduced size, low cost, easy insertion and removal, less invasive surgical technique, immediate loading ability, less chair time and clinical versatility. The purpose of this study is to integrate a general use of mini implants as orthodontic anchorage in different clinical applications referring to its origins, characteristics, indications, contraindications, safe sites for their insertion and some clinical cases.